2021
DOI: 10.3389/fcell.2021.726205
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Reprogramming of the Ewing Sarcoma Tumor Microenvironment

Abstract: Ewing sarcoma (EwS) is a highly aggressive cancer and the second most common malignant bone tumor of children and young adults. Although patients with localized disease have a survival rate of approximately 75%, the prognosis for patients with metastatic disease remains dismal (<30%) and has not improved in decades. Standard-of-care treatments include local therapies such as surgery and radiotherapy, in addition to poly-agent adjuvant chemotherapy, and are often associated with long-term disability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 158 publications
(242 reference statements)
0
5
0
Order By: Relevance
“…For sarcomas to thrive in their new environment, it is of utmost importance for the PMN to protect the metastatic sarcoma cells from being apoptosed upon entering the metastatic site [ 85 ]. Exosomes produced by tumor cells can support their escape from immune surveillance [ 86 , 87 , 88 ]. Exosomes can upregulate the expression of proinflammatory factors and induce the secretion of some proinflammatory chemokines and cytokines, such as IL10, TGF-β2, and IL-35, in the tumor local inflammatory microenvironment, thus weakening antitumor immune responses [ 87 , 89 , 90 ].…”
Section: The Mechanisms Of Exosome Involvement In Sarcoma Metastasismentioning
confidence: 99%
“…For sarcomas to thrive in their new environment, it is of utmost importance for the PMN to protect the metastatic sarcoma cells from being apoptosed upon entering the metastatic site [ 85 ]. Exosomes produced by tumor cells can support their escape from immune surveillance [ 86 , 87 , 88 ]. Exosomes can upregulate the expression of proinflammatory factors and induce the secretion of some proinflammatory chemokines and cytokines, such as IL10, TGF-β2, and IL-35, in the tumor local inflammatory microenvironment, thus weakening antitumor immune responses [ 87 , 89 , 90 ].…”
Section: The Mechanisms Of Exosome Involvement In Sarcoma Metastasismentioning
confidence: 99%
“…Unlike epithelial cancers, the current understanding of the origin and contribution of CAFs in sarcomas is very limited. Studies in Ewing sarcoma 144 and osteosarcoma 145 have demonstrated that extracellular vesicles and associated cargo secreted from tumor cells drive the transformation of normal fibroblasts into CAFs. On the contrary, rhabdomyosarcoma cells do not rely on CAFs to prime the ECM for local tumor expansion, but rather produce their own ECM with minimal involvement of CAFs 146 .…”
Section: Barriers To Immunotherapy For Soft Tissue and Bone Sarcomamentioning
confidence: 99%
“…Our knowledge remains sparse for other types of solid malignancies of non-epithelial origin, e.g., in sarcomas. Except for Ewing sarcoma [42] and osteosarcoma [43], the role of CAFs in sarcomas of different origins is unclear. Further, CAFs have not been extensively studied in haematological malignancies so far.…”
Section: Fibroblasts As a Fundamental Bioactive Part Of The Majority ...mentioning
confidence: 99%